Photothermal catalytic transfer hydrogenolysis of protolignin - Hongji Li; Xiaotong Sun; Ting Li; Zhitong Zhao; Hui Wang; Xiaomei Yang; Chaofeng Zhang; Feng Wang (Nature Communications)
Abstract Photothermal catalysis is a promising strategy to combine the advantages of both thermal-catalysis and photocatalysis. Herein we achieve the protolignin conversion to aromatics via the photothermal catalytic transfer hydrogenolysis process intensified by the in-situ protection strategy. The Pd/TiO2 at 140 °C with UV irradiation can catalyze the reforming of primary alcohols to aldehydes and active H* species, which further participate in the acetalation protection of the 1,3-diol group of β-O-4 linkage and mediate the hydrogenolysis of Cβ–OAr bonds, respectively. The conversion of birch sawdust with ethanol as the hydrogen donor provides a 40 wt% yield of phenolic monomers, compared with an 11 wt% monomer yield obtained from the conversion of extracted 1,3-diol-protected lignin under the same conditions. The synergistic effect of photocatalysis and thermal-catalysis contributes to the prior cleavage of the Cβ–OAr bond before other C–O bonds. The feasibility of solar-light-driven photothermal catalytic system is demonstrated.